Weed plant species associated with the population increase of carabid beetles - Cividanes, Francisco J.; dos Santos-Cividanes, Terezinha M.; Barbosa, José C. [UNESP]; Ide, Sérgio (Elsevier, 2025)
Carabid beetles (Coleoptera: Carabidae) are important biocontrol agents of insect pests and weeds worldwide. Despite this, few studies have investigated weed seed-consuming carabids in Latin America. We studied the relationship between the abundance of weed plants and the population size of carabids in five agroecosystems located in four municipalities (Jaboticabal, Guaíra, Gavião Peixoto, and Descalvado) in northeastern São Paulo state, Brazil. The weed plants comprised a strip of weedy vegetation between a forest fragment, a soybean/maize field, or an orange orchard. Carabid beetles and weeds were sampled with pitfall traps and a square metal frame, respectively, and multiple regression analysis was used to associate the carabids and weed plants. Of the 921 individuals of 18 carabid species captured, Abaris basistriata Chaudoir, Selenophorus seriatoporus Putzeys, Pentacomia cupricollis (Kollar), and Tetracha brasiliensis (Kirby) were among the most abundant. Regarding weeds, 27 species from 11 families were identified, mostly members of the families Asteraceae and Poaceae. This study indicated that weed species can contribute to population increases of predominantly granivorous and predatory carabid beetles. The family Poaceae showed the highest association with increases in populations of carabid beetles. Cenchrus echinatus L., Melinis repens (Willd.) Zizka, and Urochloa decumbens (Stapf) (Poaceae), Chamaesyce hirta (L.) Millsp. (Euphorbiaceae), Cyperus rotundus L. (Cyperaceae), and Richardia brasiliensis Gomes (Rubiaceae) were most frequently correlated with carabids. These findings suggest lines of research on carabids that consume weed seeds and on weeds that provide refuge for carabids. Progress in these areas is essential for sustainable weed management.
Keywords: Carabid beetles; Granivorous carabid; Predatory carabid; Weed management; Weed strip